2012
DOI: 10.1158/1078-0432.ccr-11-1282
|View full text |Cite
|
Sign up to set email alerts
|

Punctate LC3B Expression Is a Common Feature of Solid Tumors and Associated with Proliferation, Metastasis, and Poor Outcome

Abstract: Purpose Measurement of autophagy in cancer and correlation with histopathologic grading or clinical outcomes has been limited. Accordingly, we investigated LC3B as an autophagosome marker by analyzing nearly 1400 tumors from 20 types of cancer, focussing on correlations with clinical outcomes in melanoma and breast cancer. Experimental Design Staining protocols were developed for automated quantitative analysis (AQUA) using antibodies vs LC3 isoform B (LC3B) and Ki-67. Clinically annotated breast and melanom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
224
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(236 citation statements)
references
References 32 publications
(45 reference statements)
9
224
0
3
Order By: Relevance
“…Our findings are in agreement with a recent study that reported high basal MAP1LC3B expression in various advanced solid tumors. 27 At this time, CQ and its analog HCQ are the only clinically relevant autophagy inhibitors and they are currently being evaluated in more than 20 clinical trials for cancer therapy. 6 Our study provides one of the first reports of the clinical safety and preliminary efficacy of the inhibition of autophagy as a novel approach to augment the efficacy of conventional anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with a recent study that reported high basal MAP1LC3B expression in various advanced solid tumors. 27 At this time, CQ and its analog HCQ are the only clinically relevant autophagy inhibitors and they are currently being evaluated in more than 20 clinical trials for cancer therapy. 6 Our study provides one of the first reports of the clinical safety and preliminary efficacy of the inhibition of autophagy as a novel approach to augment the efficacy of conventional anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, acidic stress caused inhibition of the mTOR pathway also in MCF-7 cells (data not shown), suggesting that the capacity of cancer cells to modulate autophagy following acidic stress may not be dependent only on mTOR inhibition but likely on their ability to restore their physiological pH i by extruding acids via pH-regulating systems. On the other hand, human melanoma cells rely on functional autophagy for survival and invasion (48) and increased autophagy in several human cancers, including melanoma is associated to metastasis and poor outcome (69). Interestingly, the melanoma cell line Me30966 maintained an increased autophagic flux even after a long-term (24 -72 h) cul-ture in acidic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…73 Moreover, the expression of the core autophagy gene MAP1LC3 (a marker of the autophagy process) is increased in samples of aggressive tumors and correlates with the risk of metastatic disease and with a poor patient outcome. 77,78 Autophagy promotes metastasis by limiting detachment-induced cell death (anoikis) during extracellular matrix detachment of cancer cells. 79 Autophagy also contributes to the survival of dormant disseminated tumor cells for extremely prolonged periods.…”
Section: Regulation and Role Of Autophagy In Cancer Cellsmentioning
confidence: 99%